Agility of The Secretariat General of The Ministry of Marine Affairs and Fisheries Post-Implementation of Organizational Simplification - Paramitha Prima Kusumawati; Entang Adhy Muhtar; Ida Widianingsih (Green Publisher Indonesia, 2025)
This research examines the organizational agility of the Secretariat General of the Ministry of Maritime Affairs and Fisheries (SETJEN KKP) following Indonesia's bureaucratic reform, which mandated structural simplification, position equalization, and team-based work systems to enhance public sector responsiveness. Against the backdrop of rapid technological advancements and the VUCA (volatility, uncertainty, complexity, ambiguity) environment, the research evaluates SETJEN KKP's alignment with Wolter Aghina’s agile framework across five dimensions: Strategy, Structure, Processes, People, and Technology. Using a qualitative descriptive approach, the study collected primary data through interviews and observations, supplemented by secondary data from regulations, reports, and documents. Findings indicate progress in agility, particularly through structural simplification and digital adoption (e.g., Electronic-Based Government Systems). However, challenges persist, including budget inflexibility, limited functional position mobility, and cultural resistance to change. The study highlights the need for optimized coordination, process innovation, and dynamic human resource development to realize agile transformation fully. Theoretically, it contributes to public administration literature on bureaucratic reform; practically, it offers policymakers insights into refining agile implementation in Indonesia’s public sector.